2005
DOI: 10.1002/pssb.200440032
|View full text |Cite
|
Sign up to set email alerts
|

Photoluminescence studies of Eu‐implanted GaN epilayers

Abstract: Photoluminescence (PL) of Eu-implanted GaN epilayers grown by Metalorganic Vapour Phase Epitaxy (MOVPE) was studied as a function of temperature. The implantation was done at ion energies of 75 keV, 200 keV and 350 keV with doses of 10(14) CM-2 and 10(15) CM-2. PL spectra of all samples show the emission 5 7 31 line assigned to the D-5(0)-F-7(2) transition of EU3+ in GaN to be split into three spectral components at 620.7 nm, 621.6 nm and 622.5 nm. The split lines are seen to have very different temperature de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
6
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 16 publications
2
6
0
Order By: Relevance
“…Interestingly, the P1 peak (∼617.5 nm) PL intensity shows a very different temperature behavior, with an increase up to ∼120 K, followed by a decrease up to RT, suggesting the presence of thermally activated population mechanisms. A similar PL peak was observed in GaN:Eu, , with a similar temperature behavior attributed to a possible selective population of Eu 3+ -related complex with increasing temperature . A peak at 617.6 nm was also recorded with enhanced intensity in Al 0.11 Ga 0.89 N:Eu, with respect to GaN:Eu, using above bandgap excitation .…”
Section: Resultssupporting
confidence: 71%
See 1 more Smart Citation
“…Interestingly, the P1 peak (∼617.5 nm) PL intensity shows a very different temperature behavior, with an increase up to ∼120 K, followed by a decrease up to RT, suggesting the presence of thermally activated population mechanisms. A similar PL peak was observed in GaN:Eu, , with a similar temperature behavior attributed to a possible selective population of Eu 3+ -related complex with increasing temperature . A peak at 617.6 nm was also recorded with enhanced intensity in Al 0.11 Ga 0.89 N:Eu, with respect to GaN:Eu, using above bandgap excitation .…”
Section: Resultssupporting
confidence: 71%
“…A similar PL peak was observed in GaN:Eu, 90,76 with a similar temperature behavior attributed to a possible selective population of Eu 3+ -related complex with increasing temperature. 91 A peak at 617.6 nm was also recorded with enhanced intensity in Al 0.11 Ga 0.89 N:Eu, with respect to GaN:Eu, using above bandgap excitation. 24 In this work, the obtained peculiar temperature behavior of the P1 peak intensity allows to define two regions I and II for temperatures below 120 K and above 120 K, respectively.…”
Section: Acs Applied Nano Materialsmentioning
confidence: 84%
“…It is well established that when the ions are placed in a local crystal field environment with low symmetry, a state with J = 2, such as the 7 F 2 multiplet, suffers a maximum 5-fold splitting corresponding to the 2 J + 1 Stark levels of the degenerate state. When Eu 3+ ions are introduced in the hexagonal GaN host they often replace the Ga 3+ ions occupying substitutional (or near-substitutional) sites with a C 3 v local symmetry. ,, In such case only three closely spaced lines are expected to be observed for the 5 D 0 → 7 F 2 transition. Particularly, under this symmetry the degeneracy of a state with J = 2 cannot be fully lifted ,,, being however unfolded in a nondegenerate A level and a 2-fold degenerate E level. The fact that more than three splittings are observed for the implanted and annealed NWs implies that either the Eu 3+ ions could be located in lower site symmetry than the trigonal one or that there are more than one symmetry site/environment, resulting in different europium-related optically active centers.…”
Section: Results and Discussionmentioning
confidence: 99%
“…Highresolution PL spectroscopy at low temperature previously showed that the 622 nm line is in fact spectrally complex [49]: the line has at least 3 components. A crystal field splitting may lead to a line splitting, of course, without different sites being involved, but not in this case [50]. The first evidence for site multiplicity in GaN:Eu emerges from a comparison of PL spectra of a number of different samples taken under the same conditions of excitation: 5 mW, 325 nm, 15 K; a selection of such spectra is shown in Figure 5: samples prepared differently show measurably different spectral profiles.…”
Section: Optical Studies (Pl Ple CL Time-resolved)mentioning
confidence: 99%